Comparative Transcriptomic and Proteomic Analyses Identify Key Genes Associated With Milk Fat Traits in Chinese Holstein Cows - Zhou, Chenghao; Shen, Dan; Li, Cong; Cai, Wentao; Liu, Shuli; Yin, Hongwei; Shi, Shaolei; Cao, Mingyue; Zhang, Shengli (Frontiers in Genetics, 2019)
Milk fat is the most important energy substance in milk and contributes to its quality and health benefits. However, the genetic mechanisms underlying milk fat synthesis are not fully understood. The development of RNA sequencing and tandem mass tag technologies has allowed the identification of eukaryotic genes associated with complex traits. In this study, we used these methods to obtain liver transcriptomic and proteomic profiles of Chinese Holstein cows (n = 6). Comparative analyses of cows with extremely high vs. low milk fat percentage phenotypes yielded 321 differentially expressed genes (DEGs) and 76 differentially expressed proteins (DEPs). Functional annotation of these DEGs and DEPs revealed 26 genes that were predicted to influence lipid metabolism through insulin, phosphatidylinositol 3-kinase/Akt, mitogen-activated protein kinase, 5' AMP-activated protein kinase, mammalian target of rapamycin, and peroxisome proliferator-activated receptor signaling pathways; these genes are considered as the most promising candidate regulators of milk fat synthesis. These results enhance our understanding of the genetic basis and molecular mechanisms of milk fat synthesis, which could lead to the development of cow breeds that produce milk with higher nutritional value.